PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION BERBANTU MEDIA KANTONG BILANGAN TERHADAP HASIL BELAJAR SISWA MATERI PENJUMLAHAN KELAS II SD NEGERI 3 GENENGSARI KEC.KEMUSU KAB.BOYOLALI - Dewi Rochmana; Kartinah; Rofian (STKIP Subang, 2023)
The background that drives this research is the low learning outcomes of students on addition material. Students tend to memorize addition without knowing the concept of addition. This is evidenced by the difficulty of students answering questions given by teachers regarding addition material and the lack of teachers in applying learning models and learning media makes learning objectives have not been achieved properly. The problem in this study is whether the Realistic Mathematics Education Learning Model Assisted by Number Pocket Media on Student Learning Outcomes Class II Summation Material SD Negeri 3 Genengsari Kec.Kemusu Kab.Boyolali? The purpose of this study is to determine the influence of the Realistic Mathematics Education learning model assisted by number bag media on student learning outcomes of grade II summation material at SD Negeri 3 Genengsari kec. Kemusu Kab.Boyolali. This type of research is quantitative. This research design uses Pre Experimental Design in the form of One Group Pretest Posttest Design. The population in this study was grade 3 students of SD Negeri 3 Genengsari. The sample used was grade II students of SD Negeri 3 Genengsari consisting of 16 students. The sampling technique in this study is using saturated sampling. Data in this study were obtained through interviews, observations, tests and documentation. The data analysis technique used in the initial analysis is the normality test. The final analysis uses normality tests, hypothesis tests, and learning due diligence. The average learning outcomes of students who showed learning without using Realistic Mathematics Education learning assisted by pocket media (pretest) was 64,375%. While the average learning outcomes of students after being given treatment (posttest) using Realistic Mathematics Education learning assisted by pocket media as much as 78,125 %. This is reinforced by the results of paired t-test calculations, it can be concluded that the t-test paired in the pretest and posttest results in a significance value of 0.002 < 0.05, then H0 is rejected and Ha is accepted or it can be said that the Realistic Mathematics Education Learning Model Assisted by Number Pocket Media has an effect on improving the learning outcomes of grade II students of the addition material of SD Negeri 3 Genengsari. Based on the results of this study, suggestions that researchers can convey should be that teachers should use the Realistic Mathematics Education learning model used in addition material learning activities.